Effects of ultraviolet radiation on collagen - Chen, Siying. (2009)
The stiffness and tensile strength of collagen fibres are profoundly influenced by crosslinking density. Ultraviolet radiation is a viable way of producing the cross-links but effects vary with type of ultraviolet light used and duration of exposure. Moreover, prolonged exposure to UV radiation would cause protein degradation and loss of function. In this study, ultraviolet light of two different wavelengths, UVA (365 nm) and UVC (254 nm), were compared to determine their cross-linking capabilities on sheep ligament collagen fibres. In addition, collagen fibres were irradiated for 3 different time periods to determine the effects of brief and prolonged exposure to ultraviolet light. Fibres exposed to UVA displayed mechanical properties superior to both native and UVC treated fibres. Increasing irradiation time brought about initial increase in strength due to formation of cross-links. However, after 30 minutes of exposure, chain cleavages weakened the fibre. Although increasing cross-linking density would have made the fibres brittle to tensile loading, SEM images showed that failure of fibres was a result of fibre pull-out instead of abrupt fractures. Because collagen is an important protein in abundant throughout our body and is a promising biomaterial, data from this study may help in the understanding of collagen and how ultraviolet light will affect collagenous tissues.